2020
DOI: 10.1177/1971400919900635
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for acute stroke in pregnancy

Abstract: Several recent randomised control trials have shown adjunctive endovascular mechanical thrombectomy to be an effective and safe treatment for acute stroke superior to medical therapy alone. Despite this, questions remain over certain groups of patients that have been excluded from these studies, such as pregnant women. We believe this is a topic of increasing clinical significance with minimal data in the literature. In this article we discuss stroke in pregnancy and highlight the important technical considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…24 Given the favourable outcomes of patients who undergo mechanical thrombectomy for AIS, the next way forward is to develop ways to make its use more reasonable and safer in higher risk cohorts, such as pregnant women. 25 All things considered, it can be concluded that the service in Malta is managing to achieve favourable outcomes for patients treated with mechanical thrombectomy for AIS. The service is still being developed and aims to achieve better outcomes to continue helping patients return back to their previous functional state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Given the favourable outcomes of patients who undergo mechanical thrombectomy for AIS, the next way forward is to develop ways to make its use more reasonable and safer in higher risk cohorts, such as pregnant women. 25 All things considered, it can be concluded that the service in Malta is managing to achieve favourable outcomes for patients treated with mechanical thrombectomy for AIS. The service is still being developed and aims to achieve better outcomes to continue helping patients return back to their previous functional state.…”
Section: Discussionmentioning
confidence: 99%
“…Given the favourable outcomes of patients who undergo mechanical thrombectomy for AIS, the next way forward is to develop ways to make its use more reasonable and safer in higher risk cohorts, such as pregnant women. 25…”
Section: Discussionmentioning
confidence: 99%